Criminal Vocabulary as a Phenomenon Criminal Subculture - Chaplyk, Mykola (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
Jargon as an element of functioning of the criminal world and as a part of the criminal subculture is considered in the paper. The concepts of "argot" and "jargon" and their significance are presented. An attempt to consider the origin of the jargon of the criminal world and its evolution is executed. In particular, impact of different languages on formation of the criminal argot, changes in it in different historical eras are considered. The point of view on the impact of the so-called peddlers’ jargon to the development of domestic criminal argot is proved. Its role and importance for the functioning of crime is revealed. The examples of the spread of crime argot not only in the criminal environment are presented. The reasons of the current trends with the spread of criminal argot in society are explained. Characteristics of the pathways of dissemination of the language of the criminal world in society are presented.